Analisis Sistem Rekrutmen Karyawan di RSU Muhammadiyah Ponorogo: Proses, Tantangan, dan Praktik Terbaik dalam Seleksi SDM - Katmiatin Katmiatin (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Employee recruitment systems are a critical component in maintaining the quality of human resources (HR) in healthcare institutions, particularly in Muhammadiyah General Hospital (RSU Muhammadiyah), which is based on Islamic values. This study aims to describe the process, challenges, and best practices in the employee recruitment system at RSU Muhammadiyah Ponorogo. Using a qualitative approach, data were collected through in-depth interviews with the Human Resources Development (HRD) team and key stakeholders, direct observation of the selection process, and relevant document studies. Data analysis was conducted thematically, revealing that the recruitment stages at RSU Muhammadiyah Ponorogo include identifying HR needs, administrative selection, written tests, in-depth interviews that assess not only technical competence but also alignment with Islamic values and culture, and health checks. One of the main challenges in this process is finding candidates who possess not only sufficient technical competence but also integrity and ethics that align with Muhammadiyah values. Additionally, ensuring transparency and objectivity in the selection process is crucial to ensure fairness and professionalism. The best practices identified in this study highlight the importance of close coordination between the HRD team and hospital management to create an effective and efficient recruitment process. Emphasizing value-based selection, which not only considers competence but also character and integrity, is key to producing a high-quality workforce. The findings stress the need for strengthening value-based selection to produce employees who are not only professional but also reflect the vision, mission, and Islamic values upheld by RSU Muhammadiyah Ponorogo.